PENGARUH GAYA HIDUP DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (PADA KONSUMEN KLINIK KECANTIKAN LARISSA AESTHETIC CENTER SEMARANG) - Mia Darmianti; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2019)
This research was conducted with the aim to find out the influence of lifestyle and values customer loyalty to customers through customer satisfaction as an intervening variable. This research was conducted on products and treatments at the Larissa Aesthetic Center beauty clinic Semarang. The sample of this study was 100 respondents with criteria of made purchases or treatments at the Larissa Aesthetic Center at least twice in the last three months. This study consisted of 4 variables, 23 indicators and 5 hypotheses. The analytical tool used is SPSS 20 for windows with a validity test, reliability test, correlation coefficient test, determination coefficient, simple and multiple regression analysis, significance test (t and F test), and multiple tests. The results of this study indicate that there is a positive influence of lifestyle variables and customer value on customer loyalty through customer satisfaction. The customer value variable has the greatest influence at 40,2.6% while the lifestyle variable has an influence of 19,3% which simultaneously stimulates lifestyle variables and the customer value has a contribution of 45,6% on customer loyalty through customer satisfaction at Larissa Aesthetic Center. Based on these results it is suggested that Larissa Aesthetic Center needs to make improvements in terms of increasing high professionalism by all employees, improving quality in order to compete with other beauty clinics, increasing service level and providing information to customers in a manner periodically regarding the latest info.